THE ROLES OF MOTIVATION (SELF-EFFICACY AND TASK-VALUE), WRITING KNOWLEDGE, SKILLS, AND STRATEGIC APPROACH TO STUDENTS' PERFORMANCE IN WRITING - Masrul, Masrul; Yuliani, Sri (Universitas Islam Lamongan, 2023)
Writing is challenging with many variables to consider, including learners’ knowledge, motivation, strategic behaviors, and skills. This study investigates the relationship between writing knowledge, strategic approach, skills, and motivation (self-efficacy, task value) on students’ performance in writing. The samples were 100 students (40 males and 60 females) from the Department of English Education at the University of Riau, Indonesia. They were between 18 and 24 years old. Researchers used a correlation approach. The finding of this study indicates that motivation (self-efficacy and task value), strategic approach, skills, and writing knowledge have a close and significant relationship one another. It is also proven that motivation (self-efficacy and task value), strategic approach, writing skills, and writing knowledge strongly influence the students' performance in writing. Keywords: writing performance, motivation, writing knowledge, skills, strategic approach